EVALUASI PENDIDIKAN DASAR TINGKAT KECAMATAN DI KABUPATEN BANYUASIN - Suripto Suripto (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Education is the main factor that determines the success of development. Regional autonomy has given authority to the field of basic education to the local government district. Equitable and expanded access to education is one indicator of the success of education development. How is the success rate of primary education in Banyuasin Districts? This study uses descriptive method with literature study. The analytical tool used is the Analytical Hierarchy Process (AHP). The results show that the Banyuasin Sub District III, Banyuasin Sub District I and Talang Kelapa Sub District are the best in basic education.